2018
DOI: 10.1152/japplphysiol.00133.2018
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of hamstrings is individual specific and is related to motor performance

Abstract: The torque-sharing strategies between synergistic muscles may have important functional consequences. This study involved two experiments. The first experiment ( n = 22) aimed 1) to determine the relationship between the distribution of activation and the distribution of torque-generating capacity among the heads of the hamstring, and 2) to describe individual torque-sharing strategies and to determine whether these strategies are similar between legs. The second experiment ( n = 35) aimed to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…Importantly, this methodological issue does not explain the higher shear modulus values obtained for BF and SM compared to ST, as the maximal shear wave velocity is reached when the probe is along the fibers . Therefore, this influence is likely marginal between SM and BF which present close pennation angle . Thus, the lower shear modulus values for ST compared to SM and BF could result from the variance in biomechanical loads for each hamstring muscle.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, this methodological issue does not explain the higher shear modulus values obtained for BF and SM compared to ST, as the maximal shear wave velocity is reached when the probe is along the fibers . Therefore, this influence is likely marginal between SM and BF which present close pennation angle . Thus, the lower shear modulus values for ST compared to SM and BF could result from the variance in biomechanical loads for each hamstring muscle.…”
Section: Discussionmentioning
confidence: 96%
“…30 Therefore, this influence is likely marginal between SM and BF which present close pennation angle. 31 Thus, the lower shear modulus values for ST compared to SM and BF could result from the variance in biomechanical loads for each hamstring muscle. During running, Schache et al 32 showed that BF exhibits the largest peak strain while SM produced the highest peak force and performed the largest amount of work.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the hamstring muscles generate large opposing forces during high-speed running [96] while also playing a role in the production of dynamic stability at the knee [82]. Based on the present research, the possibility exists that changes in muscle coordination strategies may cause one or more hamstring muscles to be disproportionately activated [70], possibly increasing metabolic demand and thus prematurely fatiguing the overactive muscles [70]. With fatigue it appears that lower limb stiffness decreases [85], which could cause the adoption of a "Groucho" running pattern, associated with reduced movement efficiency and greater joint moments of force.…”
Section: Discussionmentioning
confidence: 66%
“…In accordance with this, Avrillon et al [70] observed individual-specific differences in hamstring muscle coordination strategies and hypothesized that these individual muscle coordination strategies might have functional consequences. For example, if one muscle is activated to a greater extent than required by the task, which is inevitably the case when activation between synergists is imbalanced, its metabolic demand would be higher and fatigue would develop sooner, which the authors suggested could increase injury risk [70]. Conversely, fatigue influences muscle activation patterns during maximum sprint running [71] so that neuromuscular coordination is altered under fatiguing conditions.…”
Section: Interactions Between Fatigue Hamstring Muscle Activation Anmentioning
confidence: 77%
See 1 more Smart Citation